Efek Penggunaan Probiotik Topikal Terhadap Ekspresi MMP-13 dan Kolagen III pada Lapisan Dermis Tikus yang Dipapar Sinar Ultraviolet-B - Vita M. Tarawan; Anissa Anissa; Endang Sutedja; Ronny Lesmana (Universitas Padjadjaran, 2016)
Proses penuaan kulit terjadi karena kombinasi penurunan kapasitas proliferasi sel-sel kulit, berkurangnya sintesis matriks dermis, dan peningkatan ekspresi enzim yang mendegradasi matriks kolagen. Penelitian ini merupakan eksperimental laboratorik, menggunakan 24 ekor tikus jantan galur Sprague-Dawley sebagai objek penelitian. Pada kelompok perakuan, kulit dorsal kedua kelompok dicukur, kemudian diberikan paparan sinar UVB seminggu tiga kali selama 4 minggu dengan dosis total penyinaran 840 mJ/ cm2. Kulit kelompok perlakuan diolesi krim Lactobacillus plantarum FNCC 0020 yang tidak bereplikasi, sehari 2 kali dengan komposisi aplikasi topikal koloni 247,27x107, sedangkan kelompok kontrol tidak diolesi apapun. Hasil penelitian diperoleh, baik intensitas, distribusi, maupun histoskor MMP-13 antara kelompok perlakuan dan kelompok kontrol tidak menunjukkan ada perbedaan yang bermakna (p>0,05). Intensitas kolagen III baik pada kelompok perlakuan maupun kontrol semua mempunyai derajat kuat, sedangkan distribusi kepadatan kolagennya paling rendah 20–50% dan tertingginya di atas 80%. Perbandingan distribusi kepadatan kolagen III secara statistik sangat bermakna (p<0,01). Pemberian krim topikal L. plantarum FNCC 0020 meningkatkan ekspresi distribusi kepadatan kolagen III namun tidak menurunkan ekspresi MMP-13. Kata kunci: Lactobacillus plantarum, kolagen, (matrix metalloproteinases) MMP13 Effect of Topical Probiotic on MMP-13 and Collagen III Expression in The Dermis Layer of Male Rats Irradiated with Ultraviolet-B Abstract Nowadays, there is a big interest in the use of topical probiotic preparations for skin health. One of the probiotics therurapeutic benefits is used as anti-aging. During aging, there is stimulation of activator protein-1 (AP-1) which is a transcription factor that inhibits the production of collagen and AP-1 supports the breakdown of collagen by enzymes called matrix metalloproteinases (MMPs). As administration of oral Lactobacillus plantarum could inhibit skin aging by lowering the activity of MMP, so the collagen degradation can be derived so probably topical use of Lactobacillus plantarum may give more prominent effects. We used 24 male rats Sprague-Dawley strain as research objects. This study was divided into two groups, the treatment and control groups. The shaved dorsal skin of rats were irradiated with UVB three times a week for 4 weeks with total irradiation dose of 840 mJ/cm2. Skin cream, containing 247.27x107 CFU non-replicating Lactobacillus plantarum FNCC 0020, was smeared on the treatment group, two times daily, whereas the control group did not receive any treatment. Skin biopsies were done at the end of the study for examination of MMP-13 and collagen III expressions. Intensity, distribution, and histoscore of MMP-13 between the treatment and the control group showed no significant difference (p>0.05). The treatment group showed a significant different in the intensity of collagen III with the density distribution of 20–50% and the highest density was 80% (p<0.01). Administration of topical cream L. plantarum FNCC 0020 increased the expression of collagen III density distribution, but not the MMP-13 expression.Keywords: Collagen, Lactobacillus plantarum, (matrix metalloproteinases) MMP13